2020
DOI: 10.1021/acs.nanolett.0c02999
|View full text |Cite
|
Sign up to set email alerts
|

Anomalies of Ionic/Molecular Transport in Nano and Sub-Nano Confinement

Abstract: Understanding and exploring the transport behaviors of ions and molecules in the nano and sub-nano confinement has great meaning in the fields of nanofluidics and basic transport physics. With the rapid progress in nanofabrication technology and effective characterization protocols, more and more anomalous transport behaviors have been observed and the ions/molecules inside small confinement can behave dramatically differently from bulk systems and present new mechanisms. In this Mini Review, we summarize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 74 publications
0
89
0
Order By: Relevance
“…The role of nanoconfinement on the viscoelasticity of the materials, as well as the bond exchange rate in nanometer thin films compared to bulk materials, needs further investigation. There is a large body of work on polymer films which show deviations in physical and dynamic properties when their thickness is below a critical length scale which can vary from 2 to 200 nm 50,51 . At present, it is unknown if the dynamics or modulus are altered in the dyn-PDMS films.…”
Section: Discussionmentioning
confidence: 99%
“…The role of nanoconfinement on the viscoelasticity of the materials, as well as the bond exchange rate in nanometer thin films compared to bulk materials, needs further investigation. There is a large body of work on polymer films which show deviations in physical and dynamic properties when their thickness is below a critical length scale which can vary from 2 to 200 nm 50,51 . At present, it is unknown if the dynamics or modulus are altered in the dyn-PDMS films.…”
Section: Discussionmentioning
confidence: 99%
“…In 1970s, the concept of energy conversion system based on the electrodynamic effect was proposed by Osterle's, Burgreen's and Nakache's groups [223][224][225][226]. It was expected that new findings pave the way for the energy conversion system of micro/nano fluid devices based on the electrodynamic effect more and more [227]. However, numerous investigations have indicated that the efficiency of actual energy conversion related to the conversion system based on the electrodynamic effect is relatively low and this issue has restricted its application as power devices and so on [228,229].…”
Section: Electrokinetic Energy Conversionmentioning
confidence: 99%
“…Nanofluidics is a research field that explores the transport of fluids, gases, and ionic species at the nanometre scale. [1][2][3][4] This enables the precise regulation of transported substances within confined spaces and is especially important for high-resolution sensing, disruptive technologies targeting the water-energy nexus and macro-/biomolecular analysis. Of particular interest is the study of ion transport in nanofluidic devices.…”
Section: Introductionmentioning
confidence: 99%